Agroecological transitions of pastoralism: A discussion of key concepts and an essay for explaining the current dynamics using a political economy lens - Frija, Aymen; Carpentier, Irene; Postigo, Julio; Alary, Veronique; Ouerghemmi, Hassen; Dhehibi, Boubaker (International Center for Agricultural Research in the Dry Areas, 2024)
This presentation discusses the agroecological transitions of pastoralism, emphasizing the complexities and dynamics within this framework, particularly in North Africa. It explores the paradoxical relationship between pastoralism and agroecology, highlighting the need for a nuanced understanding of diverse pastoral identities and practices. The research focuses on a case study from Beni Khedache in southern Tunisia, identifying enablers and barriers to transformative changes in pastoral systems. Methodological challenges are addressed, alongside the socio-political influences shaping these transitions. The findings underscore the importance of recognizing the diversity of pastoral systems and advocating for holistic approaches that consider socio-political drivers to foster sustainable transitions in pastoralism.